2020
DOI: 10.1016/j.heliyon.2020.e04183
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation and production of alpha amylase from thermophilic Bacillus spp. and its application in food waste biodegradation

Abstract: This study employed Bacillus spp. with α-amylase production isolated from Malaysian hot spring for domestic kitchen food waste treatment contained grains, vegetables, chicken and tuna that mimic the food waste discharge from domestic kitchens in Malaysian household. Results showed that Bacillus licheniformis HULUB1 and Bacillus subtilis SUNGB2 possess excellent amylolytic properties. Highest α-amylase activity was obtained when both isolates were cultivated at pH 6.0 and 65 C with concentrations of 18.15 U/mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 45 publications
4
26
0
2
Order By: Relevance
“…One of the possible mechanisms of the HPB to degrade food solids is through sugar biodegradation in which glucose is converted into carbon dioxide and water, thus reducing the TS of FW ( Coker, 2014 ). These results are in agreement with those recently stated by An et al, 2018 , Msarah et al, 2020 who reported the reduction of the solid content of FW by more than 2% and 43% by Bacillus spp. inoculation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…One of the possible mechanisms of the HPB to degrade food solids is through sugar biodegradation in which glucose is converted into carbon dioxide and water, thus reducing the TS of FW ( Coker, 2014 ). These results are in agreement with those recently stated by An et al, 2018 , Msarah et al, 2020 who reported the reduction of the solid content of FW by more than 2% and 43% by Bacillus spp. inoculation.…”
Section: Discussionsupporting
confidence: 94%
“…HPB species that are commonly associated with FW treatments include Bacillus spp., Brevibacillus spp., Paenibacillus spp., Pseudomonas spp. and Klebsiella spp., as they are able to secrete manifold hydrolases, particularly amylase, cellulase, protease and lipase ( Awasthi et al, 2018 , Choi et al, 2002 , Li et al, 2014 , Msarah et al, 2020 , Ren et al, 2020 ). The present study was designed to improve FW biodegradation using locally isolated HPB as an inoculant in a domestic FWB application for potential commercial purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Several Bacillus strains have been used commercially as probiotics for humans and animals [ 9 ]. In addition, Bacillus was reported to possess amylase and proteolytic activity, as well as antibacterial activity [ 10 , 11 ]. Due to these enzymatic activities, Bacillus has been used as starter cultures for protein, and/or amylase-rich fermented food such as fermented soybean and contributes to the sensory properties of the final products [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hot springs are one of the most important habitats for thermophilic microorganisms (Aanniz et al 2015). Therefore, thermophilic microorganisms attract the attention of researchers as an important source of new and high-temperature resistant enzymes such as xylanases, DNA polymerases, amylases, cellulases, phytases, chitinases, proteases, lipases, and pectinases (Falcicchio et al 2021, Lee et al 2010, Luo et al 2017, Msarah et al 2020, Tango and Islam 2002. Although the necessary equipment and approaches have changed in parallel with the development of molecular biology in the determination of microorganisms that produce these enzymes in recent years, it is still important to perform physiological, morphological, and biochemical analyzes for pure culture isolation studies (Abdollahi et Turkey is one of the world's most important countries because of its many thermal water reserves (Oztas Gulmus and Gormez 2020b).…”
Section: Introductionmentioning
confidence: 99%